2020
DOI: 10.13057/nusbiosci/n120106
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic activity of Dendrophthoe pentandra as a potential bioherbicide to inhibit seed germination and seedling growth of Eleusine indica

Abstract: Abstract. Alharits L, Hemelda NM, Yasman, Handayani W. 2020. Allelopathic activity of Dendrophthoe pentandra as a potential bioherbicide to inhibit seed germination and seedling growth of Eleusine indica. Nusantara Bioscience 12: 33-39. Dendrophthoe pentandra (L.) Miq. is a common parasitic plant in Southeast Asia. As a parasitic plant, it exhibits phytochemicals important for infecting its host, which may be potential as bioherbicide. This study was aimed to evaluate allelopathic activity of D. pentandra (ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Almost all the parts of the D. pentandra have been used traditionally for traditional medicinal and alternative medicinal purposes. For example, the extract from D. pentandra leaves has been used for diabetic and aging-related diseases due to its antidiabetic [1,19] and antioxidant properties [1,[4][5][6][7][8][9][10]. Moreover, D. pentandra flowers, when extracted, have also been studied due to their antioxidant properties [5].…”
Section: Rootsmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all the parts of the D. pentandra have been used traditionally for traditional medicinal and alternative medicinal purposes. For example, the extract from D. pentandra leaves has been used for diabetic and aging-related diseases due to its antidiabetic [1,19] and antioxidant properties [1,[4][5][6][7][8][9][10]. Moreover, D. pentandra flowers, when extracted, have also been studied due to their antioxidant properties [5].…”
Section: Rootsmentioning
confidence: 99%
“…For example, the extract from D. pentandra leaves has been used for diabetic and aging-related diseases due to its antidiabetic [1,19] and antioxidant properties [1,[4][5][6][7][8][9][10]. Moreover, D. pentandra flowers, when extracted, have also been studied due to their antioxidant properties [5]. Interestingly, Pramestya et al [29] found that D. pentandra flowers tend to accumulate more secondary metabolites than other parts.…”
Section: Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…In folklore, DF is called “Banda” ( Ghirtlahre et al, 2015 ) and “Vanda” ( Khatoon et al, 2011 ), while DP is called “Benalu” ( Elsyana et al, 2016 ). Additionally, DF and DP are also commonly known as Indian mistletoe and Indonesian mistletoe, respectively in Englishbecause their distribution is concentrated in India and Indonesia, respectively ( Sinoriya et al, 2011 ; Lim et al, 2017 ; Alharits et al, 2020 ; Singh et al, 2020 ; Bhagat and Kondawara, 2021 ; Yapa et al, 2021 ). Moreover, they are rarely present in other countries like Thailand ( Kwanda et al, 2013 ), China ( Guo and Ren, 2019 ), and Bangladesh ( Hasan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…concentrated in India and Indonesia, respectively (Sinoriya et al, 2011;Lim et al, 2017;Alharits et al, 2020;Singh et al, 2020;Bhagat and Kondawara, 2021;Yapa et al, 2021). Moreover, they are rarely present in other countries like Thailand (Kwanda et al, 2013), China (Guo and Ren, 2019), and Bangladesh (Hasan et al, 2018).…”
mentioning
confidence: 99%